METHODS OF TEACHING ECONOMIC TERMINOLOGY TO STUDENTS OF ECONOMICS BASED ON THE CVI (CONTENT AND VOCABULARY INTEGRATED) APPROACH - Zairova Madina (TADQIQOTLAR, 2025)
Abstract: This article explores effective methods of teaching economic terminology to students of economics through the CVI (Content and Vocabulary Integrated) approach, which emphasizes the simultaneous development of subject knowledge and professional vocabulary. The study highlights how integrating economic content with targeted vocabulary instruction enhances learners’ comprehension, retention, and practical use of specialized terms. Drawing on contemporary pedagogical theories and classroom practices, the article examines strategies such as contextualized reading, task-based learning, case studies, collaborative activities, and authentic materials related to economic discourse. The findings suggest that the CVI approach promotes deeper conceptual understanding, supports communicative competence in professional contexts, and increases students’ motivation by linking language learning directly to their academic field. The study underscores the value of integrated instruction for preparing economics students to operate effectively in academic and real-world economic environments.